(3WHbGJ GdMfajIs
(3ChdgG (B:s
(3Chdg HYZO GdOjHGLI e agPG cJGH eNJUQ ai PcQ WHbGJ GdMfajI s
(3hgh eNJUQ ai WHbGJ GdMfajI HOCI GdeDda HWHbI GdEeGe CHj MfajI GeGe GdePgH hBUMGHg hGfJgi ajg Edi WHbI c CMeO Hf SdjeGf Hf ceGd HGTG GdeJhai SfI (B940(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B98 s
Keywords: (3GdJGQjNs